2019
DOI: 10.4102/sajesbm.v11i1.271
|View full text |Cite
|
Sign up to set email alerts
|

The state of business incubation in the Northern Cape: A service spectrum perspective

Abstract: This study is useful not only in a rural South African context but also to other emerging markets that are rural and spatially complex.Business incubators are important for small, medium and micro-enterprise (SMME) development in an economy, because they assist with and accelerate the start-up, development and growth of SMMEs (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…By increasing local services production, the development of tourism may generate long-run positive spillovers on traded goods production by, for example, improving access to business services for local firms, such as finance, accounting, or consulting, by loosening local credit constraints directly (through tourism revenues), or by facilitating contacts and business networks. 5 In the presence of such cross-sectoral agglomeration economies, tourism can give rise to gains in manufacturing productivity that would not have occurred otherwise.…”
mentioning
confidence: 99%
“…By increasing local services production, the development of tourism may generate long-run positive spillovers on traded goods production by, for example, improving access to business services for local firms, such as finance, accounting, or consulting, by loosening local credit constraints directly (through tourism revenues), or by facilitating contacts and business networks. 5 In the presence of such cross-sectoral agglomeration economies, tourism can give rise to gains in manufacturing productivity that would not have occurred otherwise.…”
mentioning
confidence: 99%
“…Firdaus et al (2019) find that incubators serve start-ups by building network services and improving the quality of information dissemination. Van der Spuy (2019) proves that business incubators can maximize the success of graduate entrepreneurs and sustainable start-ups by providing a full range of services (Murray, 2019; Halim, 2020). Gerdsri et al (2021) believe that business incubators can provide a supportive, facilitating and nurturing environment for start-ups (Amelia et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Metrics such as access to finance, equipment, and skills by the incubation centers are recommended in [31] to measure business incubators' effectiveness. The application of metrics by van der Spuy [32] on business incubators within the Northern Cape Province of South Africa showed that only one-third meet the benchmark, which might be considered a waste of government funding.…”
Section: Enabling Oi For Startups Through Incubationmentioning
confidence: 99%